China and the birth of globalization - Flynn, Dennis O. (Henry Stewart Talks, 2013)
Globalization defined, Eastern and western hemispheric isolation for over 10,000 years, Key role of end-market China in globalization’s 16th-century birth, Spanish American and Japanese mines, European intermediaries, Revolutionary ecological, epidemiological, cultural and demographic impacts globally, Reverberations over five centuries, Evidence of general technological superiority?